Husserl’s phenomenology of time — the critique by Jacques Derrida - Mackiewicz, Wojciech (Hybris, 2013)
The problem of time was very important in the theory of phenomenology. Husserl understood that this is the basis of his research. That is why phenomenology of the time was scrutinized with a great importance. Conception of non-linear time and many possibilities of philosophical re-thinking the same moment of the time were the results of that theoretical model. Reading Husserl’s works Derrida is impressed with them. His analysis of phenomenology starts with a general question: if the conception of the time contains mistakes should we still accept the entire phenomenology at all? Accordingly, French philosopher finds three moments of that theory, which are illegitimated. However Derrida doesn’t want to refuse the phenomenology. In that three problematic points he offers his own, very interesting solutions.